Leveraging Blockchain for Academic Credentialing and Student Data Management in Universities - Abhi Rafdhi, Agis; Neni Hayati, Euis (International Journal of Research and Applied Technology (INJURATECH), 2023)
This study aims to explore the potential of blockchain technology in enhancing academic credentialing and student data management within university systems. A systematic literature review methodology was employed, analyzing peer-reviewed articles published between 2018 and 2023 sourced from databases such as Elsevier, MDPI, SpringerLink, and IEEE Xplore. The findings reveal that blockchain offers significant advantages in securing academic credentials, ensuring data authenticity, and promoting transparency in record-keeping processes. By utilizing decentralized ledgers, universities can reduce fraud, streamline verification procedures, and grant students greater control over their personal academic records. These outcomes are achieved due to blockchain’s inherent features of immutability, decentralization, and smart contract automation, which collectively eliminate traditional dependencies on centralized data authorities. Furthermore, the review highlights that while blockchain adoption presents opportunities for efficiency and trust enhancement, challenges such as technical complexity, regulatory uncertainty, and integration with existing systems must be carefully addressed. In conclusion, blockchain technology holds transformative potential for revolutionizing academic administration, but successful implementation will require strategic planning, collaboration among stakeholders, and adherence to emerging legal and ethical standards. Future research should focus on real-world pilot programs and policy development to support broader adoption across higher education institutions